2014
DOI: 10.1111/php.12296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultraviolet Radiation (UVA+UVB) on Young Gametophytes ofGelidium floridanum: Growth Rate, Photosynthetic Pigments, Carotenoids, Photosynthetic Performance, and Ultrastructure

Abstract: This study investigated the effects of radiation (PAR+UVA+UVB) on the development and growth rates (GRs) of young gametophytes of Gelidium floridanum. In addition, photosynthetic pigments were quantified, carotenoids identified, and photosynthetic performance assessed. Over a period of 3 days, young gametophytes were cultivated under laboratory conditions and exposed to photosynthetically active radiation (PAR) at 80 μmol photons m(-2) s(-1) and PAR+UVA (0.70 W m(-2))+UVB (0.35 W m(-2)) for 3 h per day. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 80 publications
0
19
0
1
Order By: Relevance
“…In a previous study using Sargassum cymosum C. Agardh as a biological model to evaluate the combined effects of UV radiation and salinity, Polo et al (2014a) found that UVA and UVB together in low doses such as the ones used herein stimulated the growth rate, leading to an increase in the amount of mitochondria, which could support the metabolic energy demand required for this process. Indeed, studies with different algal species at low doses of UV radiation show that the UV level modulates diverse physiological responses besides growth through up-or downregulation, such as induction of Chl a, phenolic compounds and antioxidant activity (Polo et al 2014a), alteration in putrescine/spermidine ratio (Polo et al 2014b), variation of photosynthetic performance and accessory pigments (Simioni et al 2014, Schmidt et al 2015, and ultrastructural organization (Bouzon et al 2012, Pereira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study using Sargassum cymosum C. Agardh as a biological model to evaluate the combined effects of UV radiation and salinity, Polo et al (2014a) found that UVA and UVB together in low doses such as the ones used herein stimulated the growth rate, leading to an increase in the amount of mitochondria, which could support the metabolic energy demand required for this process. Indeed, studies with different algal species at low doses of UV radiation show that the UV level modulates diverse physiological responses besides growth through up-or downregulation, such as induction of Chl a, phenolic compounds and antioxidant activity (Polo et al 2014a), alteration in putrescine/spermidine ratio (Polo et al 2014b), variation of photosynthetic performance and accessory pigments (Simioni et al 2014, Schmidt et al 2015, and ultrastructural organization (Bouzon et al 2012, Pereira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that light influenced the accumulation of phytochemicals such as vitamin C, phenolic compounds and carotenoids, as well as glucosinolates [125][126][127][128]. It has been reported that UV-B radiation caused an induction of glucosinolate accumulation, especially of glucoraphanin and 4-methoxy glucobrassicin in broccoli sprouts and florets [129,130].…”
Section: Lightmentioning
confidence: 99%
“…This problem was done with the Rio 92 Conference and, consequently, an emission of polluting gases by the diminished world, looking for a recovery of the ozone layer. However, the studies show that the thickness of the ozone layer is recovering, but an intensity of UVR that distances from terrestrial ecosystems has not decreased , to high levels of UVR in South America .…”
Section: Introductionmentioning
confidence: 99%